sendo f(x) = 2x - 2 e g(x) = -3x - 4, o valor de f(2) + g(-2) é?
Soluções para a tarefa
Respondido por
0
Resposta:
f ( x ) = 2x - 2
f ( 2 ) = 2 . 2 - 2
f ( 2 ) = 4 - 2
f ( 2 ) = 2
g ( x ) = - 3x - 4
g ( -2 ) = - 3 . - 2 - 4
g ( -2 ) = 6 - 4
g ( -2 ) = 2
Respondido por
0
Resposta:
4
Explicação passo-a-passo:
f(x) = 2x - 2
f(2) = 2.2 - 2
f(2) = 4 - 2
f(2)= 2
g(x) = -3x - 4
g(-2) = -3.(-2) - 4
g(-2) = +6 - 4
g(-2) = 2
Portanto, f(2) + g(-2) = 4
rlckanashiro:
espero ter ajudado
Perguntas interessantes